Rethinking Encounter: intercultural interactions between parents in Australia's culturally diverse primary schools. Issue 3 (2nd July 2016) - Hewitt, Thea
ABSTRACT: This paper critically engages with the idea that everyday spaces of association can be seen as key sites in the development of intercultural understanding for diverse individuals. Drawing on research undertaken in two culturally diverse primary schools in metropolitan Melbourne, it explores the primary school as a key site for intercultural encounters between parents in Australia's culturally diverse suburbs. This paper identifies a number of barriers limiting productive intercultural encounters between parents within the primary school setting. Specifically, it shows that such encounters are limited by national narratives of diversity, the complex demands of urban life, and the social and emotional benefits of avoiding uncertain interactions with difference. The paper builds on understandings of encounter as a contingent achievement and underscores the complexity of the 'everyday' as a space of political possibility.